Intestinal Ultrasound for the Pediatric Gastroenterologist: A Guide for Inflammatory Bowel Disease Monitoring in Children: Expert Consensus on Behalf of the International Bowel Ultrasound Group (IBUS) Pediatric Committee. Issue 2 (28th October 2022) - Kellar, Amelia; Dolinger, Michael; Novak, Kerri L.; Chavannes, Mallory; Dubinsky, Marla; Huynh, Hien
Abstract : Crohn disease and ulcerative colitis are chronic inflammatory bowel diseases (IBD) often diagnosed in childhood. A strict monitoring strategy can potentially alter the disease course and facilitate early effective treatment before irreversible bowel damage occurs. Serial colonoscopy in children, the gold standard for monitoring, is impractical. Accurate, real-time, noninvasive markers of disease activity are needed. Intestinal ultrasound is an accurate, noninvasive, real-time, point-of-care, cross-sectional imaging tool used to monitor inflammation in pediatric IBD patients in Europe, Canada, and Australia. It is now emerging in a few expert centers in the United States as a safe, non-radiating, inexpensive, bedside tool used by the treating gastroenterologist for real-time decision-making. Unlike the standard biomarkers of pediatric IBD activity, C-reactive protein, and fecal calprotectin, intestinal ultrasound (IUS) facilitates disease localization, characterizes severity, extent, and accurately detects complications. Perhaps most importantly, IUS may enhance shared understanding and ease the burden of treatment decision-making for both the gastroenterologist and the patient. There is a lack of standardization for bedside IUS among pediatric gastroenterologists. The purpose is to outline a standardized approach to pediatric bedside IUS, including basic equipment requirements and technique, patient selection, preparation and positioning, technical considerations and limitations, documentation of mesenteric and luminal features of IBD, characterization of penetrating disease and strictures, and provide a proposed pediatric IUS monitoring algorithm to guide care.